A mouse model of Alzheimer's disease displays increased susceptibility to kindling and seizure‐associated death. (16th April 2015) - Chan, Jianxiong; Jones, Nigel C.; Bush, Ashley I.; O'Brien, Terence J.; Kwan, Patrick
Summary People with Alzheimer's disease (AD) are up to 10 times more likely to develop epilepsy than the age‐matched general population. However, given that only a proportion of patients with AD develop epilepsy, it is likely that additional factors may be required for the epilepsy to emerge. This study aimed to better understand the relationship between AD pathology and seizure susceptibility. It also aimed to investigate a "two‐hit" hypothesis for seizure susceptibility through amygdala kindling of rodent AD models. Aged AD mice (Tg2576 model) and wild‐type (WT) mice underwent electrical amygdala kindling. Compared with WT mice, Tg2576 mice had significantly lower afterdischarge threshold. Significantly fewer stimulations were required for the Tg2576 mice to reach the first class V seizure. Higher death rate was observed with Tg2576 mice in the kindling group. Both sham and kindled Tg2576 animals had increased levels of sprouting in the supragranular layer of the dentate gyrus compared with the WT counterparts. These findings support the "two‐hit" hypothesis and represent a potentially novel research model to help better understand the relationship between AD pathology and epilepsy.